Carbon fiber-based polymer composite via ceramization toward excellent electromagnetic interference shielding performance and high temperature resistance. (April 2020) - Li, Ying-Ming; Deng, Cong; Zhao, Ze-Yong; Han, Lin-Xuan; Lu, Peng; Wang, Yu-Zhong
Abstract: It is greatly important to shield the X-band electromagnetic radiation and meanwhile possess a high temperature resistant performance for the outer sealing materials of hypervelocity air aircrafts. In this work, novel ceramifiable electro-conductive polymer composites were prepared by incorporating glass powder (GP), mica powder (MP), organo-modified montmorillonite (OMMT), and short carbon fiber (SCF) into ethylene-vinyl acetate (EVA). The prepared EVA/GP/MP/OMMT/SCF displayed excellent electromagnetic interference (EMI) shielding performance before and after treating at 1000 °C and also had a high temperature resistant feature via the ceramization. For the EVA/GP/MP/OMMT/SCF composite with a weight ratio of 35/23/17/5/20, its EMI shielding effectiveness (SE) reached 36.0 dB at 2.6 mm thickness, and its ceramic formed at 1000 °C possessed about 30.0 dB of EMI SE. Moreover, the formed ceramic did not show any change during a vertical burning test. Mechanism for the high SE before and after high temperatures were revealed.